SPORTS DENTISTRY: KNOWLEDGE AVALIATION OF SURGERY DENTIST ABOUT SPORTS DENTISTRY (Fiep Bulletin - online, 2011)
The objective of this research was to verify the knowledge of surgery dentists about sport dentistry, especially directed to attendance of professional and amateur athletes, both in prevention, as in the treatment of diseases and traumas, becouse, is common the existence of dental problems with athletes before, during and after workouts and competitions, beside those caused by accidents from sports trauma which may compromise significantly the result of work of a long preparation of many efforts and sacrifices, and even derail a promising career. For this purpose, we developed an investigative research involving 40 surgery dentists in Tangará da Serra - MT, all accredited by the Council Regional Dental Mato Grosso - CRO / MT. The instrument for data collection were questionnaires structured with multiple choice questions. The data showed that most dentists surveyed 60% do not know the dentistry sports, 26 (equals 65%) learned about it through publications in journals, newspapers, Internet and others. Considering the specificities of the athletes, 90% of surgery dentists recognize that they require special care in dental treatment however, during dental visits, only 42.5% asked their patients if they are participating in any sport. In the survey, was verified that 65% are unaware of the anti-doping test, so they do not observe the restrictions on medication prescription that may interfere the results of athletes. It is conclude in this research that most surgery dentists do not know the sports dentistry and orofacial treatments recommended for athletes.
Keywords: Surgery Dentist; Athlete and Dentistry Sports